2017
DOI: 10.3390/v9050123
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Autophagy Receptors in Measles Virus Replication

Abstract: Autophagy is a potent cell autonomous defense mechanism that engages the lysosomal pathway to fight intracellular pathogens. Several autophagy receptors can recognize invading pathogens in order to target them towards autophagy for their degradation after the fusion of pathogen-containing autophagosomes with lysosomes. However, numerous intracellular pathogens can avoid or exploit autophagy, among which is measles virus (MeV). This virus induces a complete autophagy flux, which is required to improve viral rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…In the case of viral infection, reported that NDP52 binds to the coxsackievirus B3 viral protein VP1 and mediates VP1 ubiquitination via the K48 ubiquitin pathway. Other studies have shown that CALCOCO2 binds the nonstructural protein 2 of the Chikungunya virus to promote viral replication in humans (Judith et al, 2013), and plays a proviral role in measles viral infection (Petkova et al, 2017). In this study, our results showed that CSFV infection inhibits NDP52 expression.…”
Section: Discussionsupporting
confidence: 62%
“…In the case of viral infection, reported that NDP52 binds to the coxsackievirus B3 viral protein VP1 and mediates VP1 ubiquitination via the K48 ubiquitin pathway. Other studies have shown that CALCOCO2 binds the nonstructural protein 2 of the Chikungunya virus to promote viral replication in humans (Judith et al, 2013), and plays a proviral role in measles viral infection (Petkova et al, 2017). In this study, our results showed that CSFV infection inhibits NDP52 expression.…”
Section: Discussionsupporting
confidence: 62%
“…5.1, Step 2). This pathway is only sensitive to vaccinal/attenuated strains that utilize CD46 to infect cells [59,91,96,106,112,118]. In fact, MeV also activates autophagy by targeting an autophagy associated protein, named as immunity-associated GTPase family M (IRGM) [45,46,107].…”
mentioning
confidence: 99%
“…Measles virus (MeV) is an enveloped virus with a negative-stranded RNA genome [87], which can induce autophagy during viral infection, thereby promoting its replication [88,89]. Studies have shown that NDP52 plays an important role in regulating viral replication by binding to MeV-C and MeV-V proteins in MeV-infected cells [90]. Furthermore, the inhibition of NDP52 significantly reduces MeV replication not through the entry of the virus, but the maturation of autophagosome.…”
Section: The Role and Mechanism Of Ndp52 In Viral Infectionsmentioning
confidence: 99%